Monophasic synovial sarcoma of tongue - Agarwal Atin; Shet Tanuja; Joshi Rupali; Desai Sangeeta; Chinoy R (Wolters Kluwer Medknow Publications, 2009)
Synovial sarcoma is a well defined morphologic entity extensively researched in literature. Synovial sarcoma displays a wide spectrum of clinical presentations and histologic appearances that may give rise to diagnostic dilemmas. One such unusual site in the head and neck area is the tongue. We report a case of monophasic synovial sarcoma of the tongue in a 22-year-old male. Microscopically, this tumor mimicked a poorly differentiated carcinoma which is more common at this site though the patient was young for this type of tumor. On immunohistochemistry, neoplastic cells were positive for cytokeratin, vimentin, calponin, CD99 and bcl2. Molecular studies - viz. reverse transcriptase polymerase chain reaction revealed a SYT-SSX translocation clinching the diagnosis. This paper highlights the immunohistochemistry profile and SYT-SSX translocation which helped arrive at an accurate diagnosis only because the index of suspicion for a monophasic synovial sarcoma is high.